Regional program on animal genetic resources conservation and management in Latin America and the Caribbean - CATIE - Centro Agronómico Tropical de Investigación y Enseñanza (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica), 2014)
Sum. (En)